Transport and calorimetry study of 20% La-doped CeIn3. (18th November 2020) - Kim, Suyoung; Seo, Soonbeom; Gu, Dachun; Kim, Sung-II; Kim, In-Cheol; Park, Chan-Koo; Lee, Hanoh; Park, Tuson
Abstract: CeIn3, a prototypical antiferromagnet, is an ideal candidate for investigating the relationship between magnetism and superconductivity, as superconductivity is induced as the magnetic transition temperature ( T N ) is lowered to 0 K by applying pressure. When La is substituted for Ce, T N of CeIn3 decreases to 0 K owing to the Ce dilution effects, thereby providing an alternative route to the zero-temperature quantum phase transition. In this study, we report a combinatorial approach to gain access to the critical point by applying external pressure to 20% La-doped CeIn3 . Electrical resistivity measurements of La0.2 Ce0.8 In3 show that the T N of 8.4 K at 1 bar is gradually suppressed under pressure and can be extrapolated to 0 K at approximately 2.47 GPa, thereby showing a similar pressure dependence of T N as shown by undoped CeIn3 . The kink-like feature in resistivity at T N of CeIn3 changed to an obvious jump in the doped compound for pressures higher than 1.64 GPa, indicating depletion in the carrier density due to a gap opening. AC calorimetry measurements under applied pressure show that the size of the specific heat jump at T N decreases with increasing pressure, but any signatures associated with the gap opening are not obvious, suggesting that the pressure-induced kink-to-jump change at T N in the resistivity is not a phase transition, but rather a gradual crossover. The low-temperature specific heat divided by temperature, C / T, does not strongly diverge with decreasing temperature, but is almost saturated near the projected quantum critical point, which can be attributed to a weak enhancement in the effective mass up to 2.6 GPa.